15x-9=13x-9

Simple and best practice solution for 15x-9=13x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15x-9=13x-9 equation:


Simplifying
15x + -9 = 13x + -9

Reorder the terms:
-9 + 15x = 13x + -9

Reorder the terms:
-9 + 15x = -9 + 13x

Add '9' to each side of the equation.
-9 + 9 + 15x = -9 + 9 + 13x

Combine like terms: -9 + 9 = 0
0 + 15x = -9 + 9 + 13x
15x = -9 + 9 + 13x

Combine like terms: -9 + 9 = 0
15x = 0 + 13x
15x = 13x

Solving
15x = 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
15x + -13x = 13x + -13x

Combine like terms: 15x + -13x = 2x
2x = 13x + -13x

Combine like terms: 13x + -13x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 8x-4(-7.5)=2 | | 6x-4y= | | 2p+3p-p=9-15-6 | | 180=(x+5)(x+1)x | | 6(0.15+w)=10 | | Z-4.6=-2.2-3z | | 8q-42=-26 | | -54=6z-18 | | 3/2(2x-2)1/5= | | 2(3t-6)=10t-t-6 | | 0.3+2.6=4.4 | | (275)(373-x)(.444)=(100)(x-295)(4.184) | | 3y+10=82 | | -1/7y^7*5/8y^2 | | 5m+25=-65 | | 2x=6-y | | 3.7x-4=2.7x | | (6x-3)(-2x-14)= | | (-6x+3)(2x-14)= | | (-3x+9)(4x-2)= | | 6*9-9y=-54 | | c^2=2c+35 | | 9.7/5.9 | | y^2+100=20y | | (x+1)(x-1)(x-8)=0 | | 4z=18-26 | | (6x^3-1x^2+1)/(2x+1) | | (6x-54)/5=-3x | | 30=6r-24+3t | | 7-(-5)+4-(-3)= | | 12=-2m | | -x-(1/7)=x+(1/6)+(2/7) |

Equations solver categories